2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.gutmann
|View full text |Cite
|
Sign up to set email alerts
|

“I’m not that important”: Barriers and bolsters to student agency during conversations about the intersections of physics and ethics

Abstract: Physics has greatly impacted society, both in solving problems and perpetuating harm. Yet we rarely train physics students to grapple with their responsibilities to society by facilitating conversations about ethical issues. We developed and collected classroom video of a unit on the development of the atomic bomb. Here, we analyze a set of students' small group interactions to reveal factors that enable and limit their engagement. Enabling factors include: (a) curricular materials that elicit students' opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, this almostexclusive focus has several shortcomings. Many of these efforts focus on classroom interventions (e.g., [41,43,44]). While these interventions can impact students' beliefs (and should continue in reform efforts), they may not do enough to eliminate the obstacles that students encounter when trying to navigate between physics' cultures and their own personal backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this almostexclusive focus has several shortcomings. Many of these efforts focus on classroom interventions (e.g., [41,43,44]). While these interventions can impact students' beliefs (and should continue in reform efforts), they may not do enough to eliminate the obstacles that students encounter when trying to navigate between physics' cultures and their own personal backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…At the K-12 level, teachers can implement modules or similar units that are designed to address topics like recruiting women into physics careers [41,42] as well as systemic racial biases and microaggressions [43]. At the college level, Gutmann et al [44] created an intervention to engage students in discussions about physicists' social responsibilities. Students engaged in scaffolded dialogue about what were the responsibilities of the "expert scientists" who designed the nuclear bomb.…”
Section: B Inclusivity and Equity In Physics Educationmentioning
confidence: 99%
“…More recently, PER researchers studied the impact of a 2-week unit on the development of the atomic bomb in a modern physics class on students' development and application of ethical principles, showing that many students apply productive approaches toward the development of ethical arguments and benefit from a strong scaffolding in ethical theory even if they sometimes struggle to correctly apply the theory [26]. The team also found that practices designed to elicit students' ethical opinions and develop them through engagement with other students can bolster students' perception of agency in ethical conversations within physics [27]. Parallel attempts to integrate issues of equity and inclusion into the physics classroom have shown similarly promising results [28] - [31].…”
Section: Ethics Education In Physicsmentioning
confidence: 99%
“…In physics, racism shows up in outcomes -e.g., in the underrepresentation of Black, Indigenous, and Latinx students [14] -and in the experiences reported by Students and Scientists of Color, who are continually harmed by a neutral and objective view of science [15]; conventional images of who does physics, which can amplify stereotype threat and implicit bias [16,17]; and a culture of exclusion that marginalizes underrepresented students [13,[18][19][20]. This calls for attention to the ways in which white supremacy is operating in physics teaching and learning contexts, and thus for teacher preparation around equity and antiracism.…”
Section: Introductionmentioning
confidence: 99%